(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Nephritis (kidney inflammation) is a group of inflammatory kidney diseases in which the glomerular apparatus is damaged. In nephritis, the renal pelvis system, balls, veins and tubules are damaged.